Pengaruh Friend Attachment Terhadap Kematangan Karir dengan Self Efficacy Sebagai Mediator - Pernama, Ayu; Qudsiyah, Ummi (Kuras Institute, 2021)
The study aims to obtain empirical data and ensure the significance between friend attachment and analyze self efficacy as a mediation variable on career maturity. The research design used is correalational research design with a sample of 323 students selected by using sample random sampling technique. Data collection using the Inventory of Parent and Peer Attachment (IPPA) instruments, Career Decision Self Efficacy Scale Short Form (CDSE-SF), and Career Maturity Scale. The mediator analysis technique uses corrected bootstrap method (N=5000) with 95% confidential interval in PROCESS software. The results showed that friend attachment throught self efficacy has an influence on career maturity. The conclusion is that friend attachment has a significant indirect effect on career maturity.